2014
DOI: 10.15835/nsb619252
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of <i>Allium ursinum</i>

Abstract: The aim of the present study was to evaluate Allium ursinum leaves and flowers extract anti-inflammatory effect. Plant extract 1:1 (w:v) was prepared from A. ursinum leaves by a modified Squibb repercolation method. The in vivo anti-inflammatory effects were evaluated on a rat turpentine oil-induced inflammation (i.m. 6 mL/kg BW). The animals were randomly assigned to nine groups (n=8): negative control, inflammation, A. ursinum flower extract (AUF), A. ursinum leaves extract (AUL), indomethacin (INDO) (20 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Many cases of research have indicated that Allium species are effective in the prevention of those diseases [1,6,9,12,13,15,23,[28][29][30][31]37]. In addition, Allium species are known to have antioxidant, anti-inflammation, antimicrobial and anti-obesity properties [3,8,16,19,21,22,26,27,32,35]. The therapeutic effects of Allium are mostly attributed to sulphur compounds, especially allicin [7,24].…”
Section: Introductionmentioning
confidence: 99%
“…Many cases of research have indicated that Allium species are effective in the prevention of those diseases [1,6,9,12,13,15,23,[28][29][30][31]37]. In addition, Allium species are known to have antioxidant, anti-inflammation, antimicrobial and anti-obesity properties [3,8,16,19,21,22,26,27,32,35]. The therapeutic effects of Allium are mostly attributed to sulphur compounds, especially allicin [7,24].…”
Section: Introductionmentioning
confidence: 99%